The Thangal Kings of Malabar: A Study of Sayyid Fazal Mouladdavila and Sayyid Husain Shihabuddin as influential leaders in nineteenth century Malabar - Abdul Vahid K (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2025)
In the 19 century AD, Malabar became a center of anti-colonial resistance involving Sayyid figures such as Sayyid Fazal Mouladdavila and Sayyid Husain Shihabuddin, who served as both religious and political leaders. Rooted in the tradition of the Hadrami diaspora, they combined spiritual authority and militant activism to mobilize resistance against British colonialism. The research method used by the author is the historical method, which is divided into four stages: source collection, criticism, interpretation, and historiography. This research also analyzes colonial correspondence, British administrative reports, and local archives to reveal the role of the Sayyids in resisting colonialism, the influence of Sufi networks, and religious legitimacy among marginalized communities. The findings show how Sayyid figures navigated religious, social, and political landscapes to challenge both colonial authorities and local feudal elites. Sayyid Fazal and Sayyid Husain were not only respected spiritual leaders but also central actors in organizing sustained resistance. Their integration into local society through kinship ties and religious leadership provided grassroots support and political credibility. Their activism represents a unique model of Islamic anti-colonial leadership that operated through theological discourse and strategic community engagement, offering a more nuanced understanding of Muslim resistance in South Asia.